Aromatic antiepileptic drugs and mitochondrial toxicity: Effects on mitochondria isolated from rat liver - Santos, N. A. G.; Medina, W. S. G.; Martins, N. M.; Mingatto, Fábio Erminio [UNESP]; Curti, C.; Santos, A. C. (Pergamon-Elsevier B.V. Ltd, 2008)
Idiosyncratic hepatotoxicity is a well-known complication associated with aromatic antiepileptic drugs (AAED), and it has been suggested to occur due to the accumulation of toxic arene oxide metabolites. Although there is clear evidence of the participation of an immune process, a direct toxic effect involving mitochondria dysfunction is also possible. The effects of AAED on mitochondrial function have not been studied yet. Therefore, we investigated, in vitro, the cytotoxic mechanism of carbamazepine (CB), phenytoin (PT) and phenobarbital (PB), unaltered and bioactivated, in the hepatic mitochondrial function. The murine hepatic microsomal system was used to produce the anticonvulsant metabolites. All the bioactivated drugs (CB-B, PB-B, PT-B) affected mitochondrial function causing decrease in state three respiration, RCR, ATP synthesis and membrane potential, increase in state four respiration as well as impairment of Ca(2+) uptake/release and inhibition of calcium-induced swelling. As an unaltered drug, only PB, was able to affect mitochondrial respiration (except state four respiration) ATP synthesis and membrane potential; however, Ca(2+) uptake/release as well as swelling induction were not affected. The potential to induce mitochondrial dysfunction was PT-B > PB-B > CB-B > PB. Results suggest the involvement of mitochondrial toxicity in the pathogenesis of AAED-induced hepatotoxicity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: mitochondria; aromatic antiepileptic drugs; hepatotoxicity; phenobarbital; phenytoin; carbamazepine; arene oxides